Understanding Shock Response of Body-Centered Cubic Molybdenum from a Specific Embedded Atom Potential - Yichen Jiang; Yanchun Leng; Xiaoli Chen; Chaoping Liang (Metals)
Extreme conditions induced by shock exert unprecedented force on crystal lattice and push atoms away from their equilibrium positions. Nonequilibrium molecular dynamics (MD) simulations are one of the best ways to describe material behavior under shock but are limited by the availability and reliability of potential functions. In this work, a specific embedded atom (EAM) potential of molybdenum (Mo) is built for shock and tested by quasi-isentropic and piston-driven shock simulations. Comparisons of the equation of state, lattice constants, elastic constants, phase transitions under pressure, and phonon dispersion with those in the existing literature validate the reliability of our EAM potential. Quasi-isentropic shock simulations reveal that critical stresses for the beginning of plastic deformation follow a [111] > [110] > [100] loading direction for single crystals, and then polycrystal samples. Phase transitions from BCC to FCC and BCC to HCP promote plastic deformation for single crystals loading along [100] and [110], respectively. Along [111], void directly nucleates at the stress concentration area. For polycrystals, voids always nucleate on the grain boundary and lead to early crack generation and propagation. Piston-driven shock loading confirms the plastic mechanisms observed from quasi-isentropic shock simulation and provides further information on the spall strength and spallation process.